External Locus Of Control, Financial Attitude, Dan Financial Management Behavior - Mentari Clara Dewanti; Daisy Marthina Rosyanti; Fani Khoirotunnisa (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Generation Z's behavior in consuming goods and services has a tendency to a consumptive lifestyle, which can disrupt financial stability. Therefore, skills in managing finances must be possessed by Generation Z. Financial Management Behavior must be understood because the ability to manage finances helps to avoid a consumptive lifestyle. The focus of this study is to examine the effect of financial attitude on financial management behavior mediated by external locus of control on the consumption pattern of Generation Z, who in this study are students of the Management Department, Faculty of Economics and Business at UPN